2021
DOI: 10.1080/21655979.2021.1999555
|View full text |Cite
|
Sign up to set email alerts
|

Long non-coding RNA (LncRNA) SNHG7/ Eukaryotic translation initiation factor 4 gamma 2 (EIF4G2) involves in the malignant events of ovarian cancer cells with paclitaxel resistant

Abstract: LncRNA SNHG7 shows a strong relationship with malignant behavior of cancer cells and poor clinical outcome in cancer. The resistance of ovarian cancer for Paclitaxel seriously limits the clinical efficacy in chemotherapy for ovarian cancer patients. In this study, we investigated whether lncRNA SNHG7 was involved in Paclitaxel sensitivity of ovarian cancer as well as the underlying mechanism regulating the behavior of ovarian cancer cells with Paclitaxel resistance. The experiment results of wound healing and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…Cell cycle research revealed that EIF4G2 silencing led to a rise in cells in the G0/G1 phase and a drop in cells in the G2/M phase (36). EIF4G2 promotes cell proliferation in a variety of tissues, such as chondrocytes and ovarian cancer (37)(38)(39). EIF4G2 has also been proven to have a strong proliferative effect on human colon cancer cells, and its expression is increased in skeletal muscle after I/R (36,40).…”
Section: Discussionmentioning
confidence: 99%
“…Cell cycle research revealed that EIF4G2 silencing led to a rise in cells in the G0/G1 phase and a drop in cells in the G2/M phase (36). EIF4G2 promotes cell proliferation in a variety of tissues, such as chondrocytes and ovarian cancer (37)(38)(39). EIF4G2 has also been proven to have a strong proliferative effect on human colon cancer cells, and its expression is increased in skeletal muscle after I/R (36,40).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to their roles in epigenetic and transcriptional regulation, lncRNAs also handle post-transcriptional regulation through several approaches, including the formation of specific lncRNA-protein complexes (lncRNPs) that operate as competitive endogenous RNAs (ceRNAs) or “sponges” of microRNAs (miRNAs), thereby regulating alternative splicing, mRNA degradation and diminishing mRNA stability ( 93 97 ). Furthermore, lncRNAs regulate several other aspects of gene expression, such as the disruption of translational processes by binding to eukaryotic translation initiation factor 4 gamma 2 (EIF4G2) and post-translational regulation via protein interactions ( 98 , 99 ).…”
Section: Lncrna Biologymentioning
confidence: 99%
“…The prepared insert was positioned in the lower compartment containing the medium (500 μL). Non-invading cells were removed after 24 hours of culture, and the quantity of invasive cells was counted after staining with 0.1% crystal violet [23].…”
Section: Transwell Invasion Assaymentioning
confidence: 99%